Zr (IV) metal-organic framework based cadmium sulfide for enhanced photocatalytic water splitting. Issue 3 (June 2022) - Tang, Jing; Ma, Xiaoyun; He, Jiaxing; Liu, Xiangyue; Li, Mingde
Abstract: The application of cadmium sulfide is severely limited by photo-corrosion and electron-hole recombination. In this work, hierarchically structured Zr-based UiO-67 assembled from ultrathin nanosheets was rapidly synthesized by microwave and treated as support to disperse CdS and Pt NPs. Owing to the intimate interfacial contact between CdS and UiO-67, synthesized CdS/Pt/UiO-67 composites exhibit higher activity of hydrogen evolution than that of pure CdS under visible light irradiation. Femtosecond transient absorption spectra has been utilized to reveal the charge separation kinetics in CdS/Pt/UiO-67. In CdS/Pt/UiO-67 composites, MOF is not only used as support to disperse CdS, but also acted as electron trapping agent to reduce the recombination of photogenerated electrons and holes. This work makes us have a deeper understanding of the charge transfer between semiconductor and MOF materials. Graphical Abstract: ga1 Highlights: The novel CdS/Pt/UiO-67 was constructed in which UiO-67 was synthesized by microwave. The composite realized high photocatalytic activity in hydrogen evolution. The intimate interfacial contact improves photocatalytic activity of CdS/Pt/UiO-67. The possible reaction pathway and mechanism of HER by CdS/Pt/UiO-67 was discussed.